Procesy biznesowe marketingu jako podstawa informatyzacji zorientowanej na łańcuch wartości - Sitarska, Monika (Business Process Transaction as the Basis of Value Chain Oriented Information Technology Implementation, 2007)
The main subject of the paper is to present business processes analysis. These processes are the main decision area for managers of marketing departments. The aim of the article is also to show the optimal collection of marketing processes. The suitable information and data supply and implementation of adequate information technology will support decision and information area of marketing on every level of management in enterprises. These processes have been sorted in customer-oriented value chain, which takes into account customer needs.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Informatyka Ekonomiczna (10); 2007; nr 1150, s. 171-186